PENGARUH MEDIA PEMBELAJARAN BERBASIS APLIKASI POWTOON TERHADAP HASIL BELAJAR IPA SISWA KELAS VI DI SDN 1 KERTAYASA - Juandini, Vinika Belanita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted with the aim of knowing the learning outcomes of students in the subject of Natural Sciences before and after the use of learning media based on the Powtoon application and the influence of using learning media based on the Powtoon application on student learning outcomes. This study uses a quantitative approach with a type of pre-experimental research using a One Group Pretest-Posttest Design. The population in this study comprises all students of grade VI at SDN 1 Kertayasa, totaling 17 students. The sampling technique in this study used saturated sampling. The data collection techniques used in this study were interviews, observations, documentation, and tests. The data analysis techniques used in this study included initial stages such as validity testing, reliability testing, and final stages such as normality testing and hypothesis testing. The research results show that (1) Students' learning outcomes on the solar system material in class VI SDN 1 Kertayasa before using the powtoon application-based learning media were still low with an average score of 49.71. (2) Students' learning outcomes on the solar system material in class VI SDN 1 Kertayasa after using the powtoon application-based learning media were better with an average score of 86.76. (3) There is an effect of powtoon application-based learning media on the science learning outcomes on the solar system material in class VI SDN 1 Kertayasa of 72.37%.